1991
DOI: 10.2307/3578132
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Restriction Enzyme-Induced DNA Double-Strand Breaks in Chinese Hamster Ovary Cells by Pulsed-Field Gel Electrophoresis: Implications for Chromosome Damage

Abstract: Restriction enzymes can be electroporated into mammalian cells, and the induced DNA double-strand breaks can lead to aberrations in metaphase chromosomes. Chinese hamster ovary cells were electroporated with PstI, which generates 3' cohesive-end breaks, PvuII, which generates blunt-end breaks, or XbaI, which generates 5' cohesive-end breaks. Although all three restriction enzymes induced similar numbers of aberrant metaphase cells, PvuII was dramatically more effective at inducing both exchange-type and deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Induction of DSBs was observed beginning at 30 min, peaking around 1 h, and being undetectable by 2 h using a TUNEL assay (Nelms et al, 1998) (Figure 1a). These results are consistent with the previous work demonstrating that PvuII-induced DSBs peak around 30-60 min post-electroporation and become undetectable within the next 2 h (Ager et al, 1991). The PvuIIelectroporated cells also exhibited NF-kB activation as detected by NF-kB-dependent GFP expression, similar to TNFa stimulated conditions (Figure 1b).…”
Section: Electroporation Of Restriction Enzymes Cause Ikk and Nf-kb Asupporting
confidence: 92%
See 2 more Smart Citations
“…Induction of DSBs was observed beginning at 30 min, peaking around 1 h, and being undetectable by 2 h using a TUNEL assay (Nelms et al, 1998) (Figure 1a). These results are consistent with the previous work demonstrating that PvuII-induced DSBs peak around 30-60 min post-electroporation and become undetectable within the next 2 h (Ager et al, 1991). The PvuIIelectroporated cells also exhibited NF-kB activation as detected by NF-kB-dependent GFP expression, similar to TNFa stimulated conditions (Figure 1b).…”
Section: Electroporation Of Restriction Enzymes Cause Ikk and Nf-kb Asupporting
confidence: 92%
“…Previous studies have shown that restriction enzymes could efficiently create DSBs in the mammalian genomic DNA following electroporation (Ager et al, 1991;Kinashi et al, 1995). Induction of DSBs was observed beginning at 30 min, peaking around 1 h, and being undetectable by 2 h using a TUNEL assay (Nelms et al, 1998) (Figure 1a).…”
Section: Electroporation Of Restriction Enzymes Cause Ikk and Nf-kb Amentioning
confidence: 80%
See 1 more Smart Citation
“…If considerable rejoining and capping occur before all restitution or breakage has finished, then the pool of loose ends does not build up as much at large concentrations compared with small concentrations . This would be easy to imagine when cells are treated with restriction enzymes, which may be active in cells for prolonged periods of time (Costa and Bryant 1990, Ager et al 1991 . Now, by the way the data are being analysed, this leads to a smaller estimate for ),*/K* and to a less drastic discrepancy in Figure 5 at small concentrations .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, restriction endonucleases (REs), which can be introduced into mammalian cells by electroporation, cause DSBs at defined chromosomal locations (Bryant 1988, Ager et al . 1991, Obe et al .…”
Section: Introductionmentioning
confidence: 99%